Public Interest and Market Pressures - Mayes, David G. author. aut Link
XII, 119 p.
Keywords: Tackles the criticism that the European Community is an unbalanced arrangement, where the path to closer integration may involve an inequitable distribution of the benefits to large firms, rather than to the public at large, the less well off parts of the Community and those in employment.